INTERNALISASI NILAI-NILAI PENDIDIKAN KARAKTER PADA MASYARAKAT ADAT DAYAK NGAJU - Gita Anggraini (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Pontianak, 2016)
Character education has been a solution to resolve identity crisis for Indonesian young generation.excavation of original value from Indonesia has been a lot of tested and study.character education base local wisdom.Dayaknese Ngaju on Middle Borneo have recommendation values as character education enhancement.the study do on Pemantang village,East Kotawaringin District,Middle Borneo.the study using Qualitative Research Method,data collective:observation,interview and documentation.local wisdom embraced by the Dayaknese Ngaju on Middle Borneo is a philosophy of huma betang,habaring hurung,hatamuei lingu nalatai hapangkaja,karende malempang, the biggest love to the universe as the source of life. Internalized value process through paragon of the elders and indigenous,traditional events and enactment the Adat Law.